Development of A QR Code-Based Digital Payment System to Enhance Sales at Remu Market, Sorong City - Lidya Aprilia Jumroh; Virjayanti Lazinu; Nur Afni Khairunisa; Sabaria Sabaria; Sintha Istikomah (Jurnal Indonesia Sosial Sains, 2025)
Remu Market in Sorong faces challenges in improving transaction efficiency and easing access for consumers. The preference for fast, secure, and practical payment methods, especially in the midst of a pandemic, highlights the importance of digital payment systems. This study aims to analyze the effect of QR Code-based digital payment systems, with a focus on perceived benefits, convenience, and security, on increasing sales at Remu Market. Descriptive quantitative research method was used, with primary data collection through questionnaires distributed to 100 respondents. The results showed that the three perceptions of benefits, convenience, and security have a positive effect on the intention to use QR Code payments. The regression model shows significant contributions from each perception, with ease of use providing the greatest impact. These findings suggest that the implementation of a QR Code-based digital payment system can increase sales and transaction efficiency at Remu Market. The model explains 99.3% of the variation in intention to use, indicating a strong positive relationship between perceptions and intention to use.